Autonomic support of central hemodynamics and physical working capacity in female swimmers and runners in a one-year training cycle - Mykhaliuk, Ye. L.; Syvolap, V. V.; Horokhovskyi, Ye. Yu.; Михалюк, Євген Леонідович; Сиволап, Віталій Вікторович; Гороховський, Є. Ю.; Михалюк, Е. Л.; Сыволап, В. В.; Гороховский, Е. Ю. (Запорізький державний медичний університет, 2022)
The aim of the work is to assess dynamic changes in heart rate variability (HRV), central hemodynamics and physical performance in female swimmers at a distance of 50–200 meters and female runners at a distance of 400 meters in the preparatory and competitive periods of the training process. Materials and methods. At the beginning of the preparatory period and at the end of the competitive period, 11 female swimmers were examined, including 1 athlete – Master of Sports of Ukraine (MSU), 7 athletes – Candidate Masters of Sports (CMS), 1 – firstclass athlete, 2 – second-class athletes, and 22 female runners, including 1 athlete – Master of Sports of Ukraine of International Class (MSUIC), 3 athletes – Candidate Masters of Sports, 7 first-class athletes, 8 – second-class athletes and 3 – third-class athletes. Time- and frequency domain methods of HRV analysis were used to assess the mechanisms of heart neurohumoral regulation. Central hemodynamic parameters were examined by an automated tetrapolar rheography according to W. Kubiček et al. (1970) modified by Yu. T. Pushkar et al. (1970). Physical working capacity (PWC) was measured using a submaximal PWC170 test. The functional state index (FSI) was calculated according to the formula that we had proposed and patented.

Мета роботи – оцінювання динамічних змін показників варіабельності серцевого ритму (ВСР), центральної гемодинаміки та фізичної працездатності у представниць плавання на дистанції 50–200 м і жінок-бігунів на 400 м у підготовчому і змагальному періодах тренувального процесу. Матеріали та методи. На початку підготовчого та повторно наприкінці змагального періоду обстежили 11 плавчих (1 майстер спорту України, 7 кандидатів у майстри спорту (КМС), 1 першорозрядниця, 2 спортсменки II розряду) та 22 жінок-бігунів (1 майстер спорту України міжнародного класу, 3 КМС, 7 першорозрядниць, 8 спортсменок II розряду, 3 – III розряду). Для оцінювання стану механізмів нейрогуморальної регуляції серця використовували математичний і спектральний методи аналізу ВСР. Центральну гемодинаміку вивчали методом автоматизованої тетраполярної реографії за W. Kubiček et al. (1970) у модифікації Ю. Т. Пушкаря та співавт. (1970). Фізичну працездатність визначали з використанням субмаксимального тесту PWC170. ІФС розраховували за формулою, що запропонована та запатентована авторами.

Материалы и методы. В начале подготовительного и повторно в конце соревновательного периода обследовали 11 пловчих (1 мастер спорта Украины, 7 кандидатов в мастера спорта (КМС), 1 перворазрядница, 2 спортсменки II разряда) и 22 бегуньи (1 мастер спорта Украины международного класса, 3 КМС, 7 перворазрядниц, 8 спортсменок II разряда и 3 – III разряда). Для оценки состояния механизмов нейрогуморальной регуляции сердца использовали математический и спектральный методы анализа ВСР. Центральную гемодинамику изучали методом автоматизированной тетраполярной реографии по W. Kubiček et al. (1970) в модификации Ю. Т. Пушкаря и соавт. (1970). Физическую работоспособность определяли с использованием субмаксимального теста PWC170. ИФС рассчитывали по формуле, предложенной и запатентованной авторами.
Вегетативне забезпечення центральної гемодинаміки та фізичної працездатності плавчих і жінок-бігунів у річному циклі тренувального процесу
Вегетативное обеспечение центральной гемодинамики и физической работоспособности пловчих и бегуний в годовом цикле тренировочного процесса
Mykhaliuk Ye. L. - ORCID ID: 0000-0003-3607-7619; Syvolap V. V. - ORCID ID: 0000-0001-9865-4325
Keywords: swimming at a distance of 50–200 m; running at a distance of 400 m; women; sport qualification from third-class to Master of Sports of International Class; heart rate variability; central hemodynamics; physical performance; periods of the training process; плавання на дистанції 50–200 м; біг на дистанції 400 м; жінки; кваліфікація від III розряду до майстра спорту міжнародного класу; варіабельність серцевого ритму; центральна гемодинаміка; фізична працездатність; періоди тренувального процесу; плавание на дистанции 50–200 м; бег на дистанции 400 м; женщины; квалификация от III разряда до мастера спорта международного класса; вариабельность сердечного ритма; центральная гемодинамика; физическая работоспособность; периоды тренировочного процесса